Christian Torajan Youth in Perceiving Aluk To Dolo - Gayatri, Erin (Al-Albab, 2018)
The fascinating influence of world religion has given important impact to the existence of indigenous religion such as Aluk To Dolo within the life of the Christian Torajan Youth who live in Yogyakarta. Aluk To Dolo as one of indigenous religions in Indonesia, in fact, is almost in the position of weak as its followers are decreasing in its region of origin, Tanah Toraja of Sulawesi. It is found that only one leader is still remaining in Toraja accompanied by the practice of Rambu Solo which is also still being maintained in the region. This work is based on the view of the youth toward Alok To Dolo as the youth play an important role to determine and negotiate the inheritance of their religion including indigenous religion within their life. This article examines how Christian Torajan Youth perceive Christianity and Aluk To Dolo. Data collection is conducted through depth interview and focused group discussion with a group of Christian Torajan Youth members who stay in Yogyakarta for their studies. They are affiliated to Torajan student organizations and Torajan tribal church in Yogyakarta. This work concludes that Torajan students perceive the Aluk To Dolo as pendamping agama or the companion of religion they practice (Christianity) besides perceiving it as their cultural home base. In other words, they mean the Aluk To Dolo for cultural practices supporting their Christianity practice in their life. It is also found that the decreasing of the practice of Alok To Dolo by the students is more caused by three factors including the distance to the origin land, the influence from the Toraja tribal church, and the literatures having influence in their believe. As student, although the Christian Torajan youth are close and more influenced by literatures in Christianity (church), they also practice the teachings of the local religion to keep their cultural identity.